Impact of Rs657152 Gene Polymorphisms on Inflammatory Markers in COVID-19 Patients With Type 2 Diabetes Mellitus - Ahmed Amshawee; Maryam A. Hussain (Acta Medica Iranica)
COVID-19 has significantly affected people with pre-existing conditions, particularly those suffering from type 2 diabetes mellitus (T2DM), as it increases the risk of complications and mortality. The dysregulated inflammatory response in T2DM patients is a critical factor contributing to severe disease progression in these individuals. Recent research suggests that genetic variations, such as Rs657152 polymorphisms, could influence inflammatory markers and immune responses in T2DM patients infected with COVID-19. Understanding this genetic relationship is crucial for improving treatment strategies and predicting outcomes in this high-risk group. The present was designed to evaluate the correlation of Rs657152 gene polymorphisms with inflammatory markers in COVID-19 patients with T2DM. This study enrolled 91 participants, including 31 healthy individuals, 30 COVID-19 patients with T2DM, and 30 non-diabetic COVID-19 patients. Inflammatory markers (CRP, IL-6, D-dimer, and ferritin) were measured, and Rs657152 polymorphisms were genotyped. Statistical analysis was conducted using SPSS version 23. COVID-19 patients with T2DM showed significantly higher BMI, greater severity of COVID-19, and increased levels of inflammatory markers compared to non-diabetic patients. A significant correlation was observed between the Rs657152 polymorphisms and elevated levels of IL-6, D-dimer, and ferritin in T2DM patients (P<0.05). The polymorphisms of the Rs657152 gene may exacerbate the inflammatory response in COVID-19 patients with T2DM, contributing to increased severity of the disease.